Effectiveness of Picture Story in Improving Reading Comprehension in 5th Grade of SDS Tunas Harapan Tangerang - Fitria Nida Sugeng; Dwi Rahayu (Paradigma Lingua, 2025)
Based on the problems experienced by students at the elementary school level in English subjects, most students have poor reading comprehension so that learning becomes ineffective and boring, especially in grade 5 SDS Tunas Harapan. This study aims to improve students’ effectiveness in reading comprehension through picture story method in two classes namely: experiment class and control class. Data collection from the implementation of these activities uses quantitative data methods and quasi-experimental methods, then researchers have taken action with the picture story method through pre-test, treatment and post-test for 3 meetings. From these 3 meetings, researchers have taken data on students in grades 5B and 5C with a total sample and population of 30 students each through statistical calculations on the SPSS version 27.0.0 IBM application. The data was taken from the pre-test, post-test, and gain score values. Then the results of the data can be said to be successful after calculating data from the homogeneity test, normality test and data hypothesis test from these students.